The effect of mentoring on U.S. vs. foreign-born faculty's self-esteem and job satisfaction - Tony Lee; Doo H Lim; Johyun Kim (Adult Education Research Conference, 2017)
The purpose of this study was to explore the relationship among mentoring, self-esteem, and job satisfaction between U.S.-born and foreign-born faculty members in 21 research universities based on their country of origin, marital status, faculty ranking, tenure, and mentoring status.
Keywords: Foreign-born faculty; mentoring; self-esteem; job satisfaction